Series of 8 pictures. Hoisting the colours at 400 Old Ford Road. Sylvia Pankhurst pointing at the camera. The little boy is the grandson of George Lansbury
Series of 8 pictures. Hoisting the colours at 400 Old Ford Road. Sylvia Pankhurst pointing at the camera. The little boy is the grandson of George Lansbury.